Relationship between social support and incident hypertension in the Jackson Heart Study: a cohort study. Issue 3 (17th March 2022) - Harding, Barbara N; Hawley, Caitlin N; Kalinowski, Jolaade; Sims, Mario; Muntner, Paul; Young Mielcarek, Bessie A; Heckbert, Susan R; Floyd, James S
Abstract : Objectives: Social support may be an important mitigating factor against adverse cardiovascular outcomes by facilitating health-promoting behaviours or by buffering against the negative effects of stress. This study examined the association of social support with incident hypertension. Design: Prospective cohort study. Setting: We evaluated the association of social support with incident hypertension among participants in the Jackson Heart Study, a community-based cohort of African Americans. Participants: This study included African American adults, who were free of hypertension at baseline (2000–2004). Functional social support, structural social support and satisfaction with social support were assessed at baseline among 1516, 1240 and 1503 participants, respectively. Outcome measures: Incident hypertension was assessed at follow-up examinations in 2005–2008 and 2009–2013. Incident hypertension was defined by the first visit with systolic blood pressure ≥140 mm Hg, diastolic blood pressure ≥90 mm Hg or self-reported antihypertensive medication use. Multivariable Poisson regression was used to estimate the association of baseline social support with incident hypertension, adjusting for relevant confounders. Results: At baseline, the mean age of participants was 50 years and 64% were men. During a median follow-up time of 6.9 years, 54% of participants developed hypertension. A high level of functional social support was associated with lower risk of incident hypertension (incident rate ratio 0.64, (95% CI 0.41 to 0.97)), compared with a low level of functional social support. Level of structural social support and satisfaction with social support were not associated with hypertension risk. Conclusions: These results suggest that greater functional support may be associated with a lower risk of incident hypertension.